Reflexive Green Nationalism (RGN): A sociological antidote to the climate crisis? - Posocco, Lorenzo; Watson, Iarfhlaith (Frontiers in Sociology, 2022)
What can theories of nationalism and the nation-state tell us about climate change? Much of the available literature, including works by prominent thinkers Ulrich Beck and Bruno Latour, identify it as a collective global challenge rather than a local and national one. But is it really so? This article develops an original theoretical framework integrating the theory of “reflexive modernity”, theories of nationalism, and case studies of green nation-states. The goal is to change the observation point and search for original solutions to the climate crisis. Building on this theoretical framework, this study puts forward the following claims: (1) climate change is undeniably a global phenomenon, but its causes are national. It can be traced back to a small number of top polluting nation-states (the US, China, Russia, India, Japan and EU28) whose historical share of carbon dioxide and other greenhouse gases, the main cause for global warming, surpasses 74%; (2) Most of these nation-states are entrenched in Resource Nationalism (RN), a form of nationalism that sees the environment as a resource to exploit; (3) there exist forms of sustainable nationalism, which this study conceptualizes as Reflexive Green Nationalism (RGN); (4) the solution to climate change is local rather than global. It depends on top polluters' capacity to re-modernize and develop RGN; and (5) according to the Intergovernmental Panel on Climate Change, if emissions are not reduced by 43% by 2030, the world is likely to cross the tipping point into a global climate catastrophe. Therefore, updating these nation-states and their ideology to more sustainable forms is humanity's best shot at halting the climate crisis.